Regenerative rangeland management improves honey bee health and productivity - Busenitz, Katya M.; Schmid, Ryan B.; Lundgren, Jonathan G. (Frontiers in Sustainable Food Systems, 2025)
Rangelands support managed and endemic pollinator communities, but the way that cattle are managed in these habitats affects floral resources and habitat suitability. We placed honey bee colonies on continuously and regeneratively grazed rangelands. Regenerative rangelands had relatively higher stocking rates, animals were moved into new paddocks more frequently, and the rangeland was allowed to rest after grazing for longer than continuously grazed areas. Rangeland plant community characteristics measured monthly during the growing season included forage biomass, flowering species richness, and abundance of flowers. Monthly measurements of colony weight gain, brood production, and Varroa mite abundance were recorded. Regeneratively managed rangelands had more flowering species and greater flower abundance, and floral species richness was correlated with colony weight gain. Specifically, minimum floral species richness (indicative of periods of resource scarcity) were more influential to hive weight gain than periods of greater floral richness. Plant biomass was positively associated with brood production, and negatively associated with Varroa incidence. Rangeland pasture management was associated with the abundance and composition of the flowering plant communities, which in turn were associated with the health and productivity of honey bee colonies stationed at these sites. Our results suggest that regeneratively managed rangelands offer a tool for conserving and promoting honey bees in this region.